Modern Imaging in Neurooncology - Straube, Christoph; Bette, Stefanie; Pyka, Thomas; Einhellig, Heike; Zimmer, Claus; Schwaiger, Markus; Combs, Stephanie E. (Neurology International Open, 2017)
Imaging of intracranial neoplasms has significantly changed over the past two decades. This overview discusses the current state of diagnostic imaging for the three most common tumor types, namely gliomas, metastases and meningiomas, and describes the underlying technical principles as well as their application in diagnosis, treatment planning and follow-up.
Keywords: MRI; PET; glioblastoma; meningioma; brain metastases